A Fatigue–Reliability Analysis of Spot Welded Modified Tensile Shear (MTS) Specimens - Ertaş, Ahmet Hanifi; Akbulut, M. (Springer Science and Business Media Deutschland GmbH, 2021)
In sheet metal structures, generally the resistance spot welds (RSWs) are used as a joining method especially for its adaptability to automation, effectiveness, robustness and low cost. On the other hand, the spot-welded sheet metals operate, most of the time, under cyclic loading conditions, which lead to fatigue fracture in the structure. In order to predict and prevent fatigue damage in the spot-welded sheets properly, many factors which affect the quality of welds in the design phase are to be considered such as arbitrary shapes of the sheet metal, missing or incomplete spot welds, and abrasion of the welding electrodes etc. All these disadvantages cause deviations in the stress analysis and make it very hard to obtain uniform stress distributions. Hence deterministic computational approaches, even pure experimental investigations of spot welded structures, do not always result in reliable outputs. In that case, probabilistic approach appears to be a feasible alternative in the fatigue assessment of RSWs. In this study, a probabilistic fatigue analysis is carried out on spot welded modified tensile-shear (MTS) test specimens. In the probabilistic analysis a g-function was introduced for each case study. The results obtained through aforementioned method were shown to be in good agreement with the related studies in literature. © 2021, Springer Nature Singapore Pte Ltd.
8th International Conference on Fracture Fatigue and Wear, FFW 2020 -- 26 August 2020 through 27 August 2020 -- -- 254289
Keywords: Fatigue; Modified tensile shear (MTS) specimen; Reliability analysis; Spot weld